SmartOil: Blockchain and smart contract‐based oil supply chain management. Issue 2 (10th May 2021) - Haque, Bahalul; Hasan, Rifat; Zihad, Oahiduzzaman Mondol
Abstract: The traditional oil supply chain suffers from various shortcomings regarding crude oil extraction, processing, distribution, environmental pollution and traceability. It offers only forward flow of products with limitations in quality inspection, fraudulent information and monopolistic behavior of supply chain entities. Inclusion of counterfeiting products and opaqueness of the system urge renovation in this sector. Technological advancement can now reshape the infrastructure of the supply chain for the future. Here, a conceptual framework utilizing blockchain and smart contract to monitor the overall oil supply chain is suggested. Blockchain is a used to monitor and support the security building of a decentralized type supply chain. The Internet of Things (IoT) sensors open a broader window to track the process and attributes in real time. A methodology to support reverse traceability for each participant of the supply chain is constructed. Implementation of smart contracts is also shown with detailed analysis. The challenges of implementing such a system are further described and our framework's adaptability in the real world is validated. The paper concludes with future research scope to mitigate the restrictions of data management and maintenance with advanced working prototypes and agile systems achieving greater traceability and transparency.